Commercial agency and distribution agreements : (Kluwer Law International, 2000)
Commercial agency, distribution and franchising agreements form the backbone of cross-border commercial activity, and international lawyers are frequently confronted with issues relating to such agreements. This authoritative, practical reference work describes the law of the European Union relating to commercial agency, distribution and franchising, together with a detailed comparative analysis of the legislation and case law of the 15 Member States, Switzerland and Norway